Epicardial adipose tissue volume and annexin A2/fetuin-A signalling are linked to coronary calcification in advanced coronary artery disease: Computed tomography and proteomic biomarkers from the EPICHEART study. (January 2020) - Mancio, Jennifer; Barros, Antonio S.; Conceicao, Gloria; Pessoa-Amorim, Guilherme; Santa, Catia; Bartosch, Carla; Ferreira, Wilson; Carvalho, Monica; Ferreira, Nuno; Vouga, Luis; Miranda, Isabel M.; Vitorino, Rui; et al.
Abstract: Background & aims: The role of epicardial adipose tissue (EAT) in the pathophysiology of late stage-coronary artery disease (CAD) has not been investigated. We explored the association of EAT volume and its proteome with advanced coronary atherosclerosis. Methods: The EPICHEART Study prospectively enrolled 574 severe aortic stenosis patients referred to cardiac surgery. Before surgery, EAT volume was quantified by computed tomography (CT). During surgery, epicardial, mediastinal (MAT) and subcutaneous (SAT) adipose tissue samples were collected to explore fat phenotype by analyzing the proteomic profile using SWATH-mass spectrometry; pericardial fluid and peripheral venous blood were also collected. CAD presence was defined as coronary artery stenosis ≥50% in invasive angiography and by CT-derived Agatston coronary calcium score (CCS). Results: EAT volume adjusted for body fat was associated with higher CCS, but not with the presence of coronary stenosis. In comparison with mediastinal and subcutaneous fat depots, EAT exhibited a pro-calcifying proteomic profile in patients with CAD characterized by upregulation of annexin-A2 and downregulation of fetuin-A; annexin-A2 protein levels in EAT samples were also positively correlated with CCS. We confirmed that the annexin-A2 gene was overexpressed in EAT samples of CAD patients and positively correlated with CCS. Fetuin-A gene was not detected in EAT samples, but systemic fetuin-A was higher in CAD than in non-CAD patients, suggesting that fetuin-A was locally downregulated. Conclusions: In an elderly cohort of stable patients, CCS was associated with EAT volume and annexin-A2/fetuin-A signaling, suggesting that EAT might orchestrate pro-calcifying conditions in the late phases of CAD. Graphical abstract: Image 1 Highlights: The presence of coronary artery disease (CAD) affects the properties of the adjacent epicardial adipose tissue (EAT). We investigated how EAT volume and proteome are linked with coronary stenosis presence and coronary calcification in a cohort of elderly patients with severe aortic stenosis. EAT volume was associated with coronary calcification and EAT has a distinct proteomic profile characterized by upregulation of pro-calcifying proteins and downregulation of inhibitors of vascular calcification. EAT is not only involved in the pathophysiology of early stages of CAD but may also promote coronary calcification in late-stage CAD.